Fear, power, and politics : the recipe for war in Iraq after 9/11 - Cardaras, Mary, 1955- (Lexington Books, 2013)
The book explores the dynamic and dysfunctional relationships between the executive and legislative branches of government and the news media after the attacks of September 11, 2001. Their collective behavior led to the Iraq war in March 2003. The proper functioning of those two branches of government and the news media as watchdog was nowhere to be found. Perfect for students and those interested in politics, government, journalism, media studies/public policy, and international affairs/relations.